Repair of Site-Specific DNA Double-Strand Breaks in Barley Occurs via Diverse Pathways Primarily Involving the Sister Chromatid - Vu, Giang T.H. (American Society of Plant Biologists, 2014)
DNA double-strand break (DSB) repair mechanisms differ in their requirements for a homologous repair template and in the accuracy of the result. We aimed to quantify the outcome of repair of a single targeted DSB in somatic cells of young barley (Hordeum vulgare) plants. Amplicon sequencing of three reporter constructs revealed 47 to 58% of reads as repaired via nonhomologous end-joining (NHEJ) with deletions and/or small (1 to 3 bp) insertions. Alternative NHEJ revealed 2 to 5 bp microhomology (15.7% of cases) or new replication-mediated short duplications at sealed breaks. Although deletions outweigh insertions in barley, this bias was less pronounced and deleted sequences were shorter than in Arabidopsis thaliana. Between 17 and 33% of reads likely represent restoration of the original sequence. Depending on the construct, 20 to 33% of reads arose via gene conversion (homologous recombination). Remarkably, <1 to >8% of reads apparently display synthesis-dependent strand annealing linked with NHEJ, inserting 4 to 61 bp, mostly originating from the surrounding of breakpoints. Positional coincidence of >81% of sister chromatid exchanges with target loci is unprecedented for higher eukaryotes and indicates that most repair events for staggered DSBs, at least in barley, involve the sister chromatid and occur during S or G2 phase of the cell cycle.